Wattpad’s Role in Literature Learning: A Study - Basri Basri; Andi Febriana Tamrin (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
In this era of globalization, technology has been invented in all part of life, one of it is literature art. Wattpad is an app which is designed as a place to submit works of fiction from youth author both domestic and international. Through Wattpad, more ovels has been published and made into a film. This research aimed to know role of Wattpad in introducing the study of literary works which is novel. This Research use descriptive qualitative method, the result from this research is to show that wattpad user as a media of studying literature works can be said to be capable. The proof of this thing can be seen from the research result from Wattpad’s cognitive side which provides a literature works that is easy to understand and giving inspiration to readers to improve their imagination in learning about literary works.